Soewardi di Pengasingan: Nasionalisme versus Sosialisme - Joss Wibisono (Lembaran Sejarah, 2014)
Right from the start of his banishment to the Netherlands in fall 1913, Soewardi Suryaningrat had been trying to make the Dutch colonial government revoke this decision. For this he approached the social democrats that were actually in the opposition. But to no avail, and Soewardi became disillusioned with the social democrats. Analysing his conﬂict with the left makes clear in which direction Soewardi’s nationalism was heading. Was he just an “early Javanese-Indonesian nationalist”, or is there more to say about his brand of nationalism?